Conversazione straordinaria di Marco Pannella con Massimo Fagioli - Fagioli, Massimo; Pannella, Marco (Il sogno della farfalla, 2009)
In this heated discussion, broadcast live by Radio Radicale on 8.20.2009, the psychiatrist Massimo Fagioli and the Radical leader Marco Pannella expound their respective opinions and express convergences and divergences on important themes related to the understanding of human reality: from psychiatry to politics, religion, sexuality and civil rights.